2014
DOI: 10.1891/0886-6708.vv-d-13-00003
|View full text |Cite
|
Sign up to set email alerts
|

Does Childhood Sexual Abuse Victimization Translate Into Juvenile Sexual Offending? New Evidence

Abstract: The cycle of violence thesis posits that early exposure to maltreatment increases the likelihood of later maladaptive and antisocial behaviors. Childhood sexual abuse (CSA) specifically has been shown to increase the likelihood of sexual offending, although less is known about its linkages to other forms of crime. Based on data from 2,520 incarcerated male juvenile offenders from a large southern state, hierarchical logistic regression models suggested that CSA increased the likelihood of later sexual offendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 63 publications
3
43
0
1
Order By: Relevance
“…Adverse childhood experiences have been shown to have long-term effects on behavioral functioning and have recently been utilized by criminologists as a conceptual framework to understand antisocial development [6,12,13,14,15,16,17,18,19,20]. Using a large sample of 2520 serious male juvenile delinquents, the current study examined whether there were differential effects on crime based on the number of adverse childhood experiences that a ward experienced, whether these effects varied across race and ethnic groups, and whether the adverse childhood experiences’ association with offending depended on the commitment offense type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse childhood experiences have been shown to have long-term effects on behavioral functioning and have recently been utilized by criminologists as a conceptual framework to understand antisocial development [6,12,13,14,15,16,17,18,19,20]. Using a large sample of 2520 serious male juvenile delinquents, the current study examined whether there were differential effects on crime based on the number of adverse childhood experiences that a ward experienced, whether these effects varied across race and ethnic groups, and whether the adverse childhood experiences’ association with offending depended on the commitment offense type.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to examine how and to what degree adverse childhood experiences are associated with variance in specific forms of serious crime, including homicide and aggravated robbery. Moreover, while there is considerable evidence that sexual abuse victimization can be a distal predictor of subsequent sexual offending [17,18,19,20,21], much less is known about how poverty, physical abuse, emotional abuse, and other deprivations are linked to other forms of violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not all people who are maltreated as children become violent perpetrators in later life, experiencing abuse has been identified as a risk factor for criminality (Ardino, 2012; DeLisi, Kosloski, Vaughn, Caudill, & Trulson, 2014). Using a randomly selected sample of case file data ( n  = 120,000) from the PBNI, project 9 will examine associations between early trauma, mental health problems, and violent offending.…”
Section: Introductionmentioning
confidence: 99%
“…Support is offered by way of research that found a relationship between experiences of childhood maltreatment and violent offending (Fox, Perez, Cass, Baglivio, & Epps, 2015), rape convictions (Dhawan & Marshall, 1996), violent sexual offending (Widom & Ames, 1994), and general IPV (Ireland & Smith, 2009) in adulthood. Child sexual abuse has been revealed to be predictive of verbal and physical sexual coercion (Gámez-Guadix, Straus, & Hershberger, 2011;Lyndon, White, & Kadlec, 2007) as well as sexual assault perpetration (DeLisi, Kosloski, Vaughn, Caudill, & Trulson, 2014;Loh & Gidycz, 2006). Directly exploring the relationship between childhood exposure to violence and rape myth acceptance (RMA), recent research indicated such exposure has a significant positive effect upon attitudes towards rape, shown to be associated with proclivity for sexual violence (Debowska, Boduszek, Dhingra, Kola, & Meller-Prunska, 2015).…”
Section: Sexual Violence Attitudes and Child Abuse And Neglect (Can)mentioning
confidence: 99%